SAT0410 RADIOGRAPHIC EROSION SCORE IMPROVED WITH TARGETED URATE-LOWERING THERAPY IN A PROSPECTIVE GOUT VIETNAMESE COHORT. (June 2019) - Bardin, Thomas; Nguyen, Quang Dinh; Tran, Khoi Minh; Le, Nghia Hieu; Do, Duc Minh; Bousson, Valérie; Richette, Pascal; Resche-Rigon, Matthieu
Abstract : Background: Urate deposition in joints of patients with neglected gout leads to destructive arthropathy, with subchondral bone erosion, bone construction, and late joint space narrowing. Gouty erosions are believed to improve under urate lowering drugs (ULDs), but their course has been little studied. We therefore performed a systematic prospective study of a Vietnamese cohort started on allopurinol at inclusion. Objectives: To characterize radiographic outcome of gouty erosions under serum urtae-targeted ULD Methods: Included patients had crystal-proven gout, eGFR > 60 ml/min and were not taking ULDs at inclusion. Allopurinol was progressively increased to reach EULAR- recommended uricemia targets and patients were prospectively followed-up, in particular with sequential hand and foot antero-posterior radiographs and MTP and knee ultrasound (US) scans. Joint erosions were scored according to a validated index1, double contour thickness was evaluated by a 4 point-score. One index tophus per patient (hand or foot) was measured by US scan. Results: 100 patients (99M) with a mean age of 45.9 + 9.9 years, and median gout duration of 8 years (range 0-33) were included. 91 had clinical tophi. Mean baseline uricemia was 492 μmol/L. Median final allopurinol dose was 520 mg/day. 71 patients had evidence of urate arthropathy at baseline, 68 of the feet and 23 of the hands (all but 3 with foot involvement). 1st MTPs were predominantly involved (44 and 35 patients on the right and left sides respectively). Urate arthropathy at baseline correlated with gout duration (p=0.01), clinical tophi (p=0.0007), maximum double contour thickness and index tophus US measurement (p=0.03) by univariate analysis and with clinical tophi by multivariable analysis (p=0.03). Uricemia target <300 μmol/L was obtained in 63.6, 67.8, 70.6, and 61.0 % of patients at 3, 6, 12 and 24 months respectively. Median radiological follow-up was 12 months (range 3-49). Mean radiological erosion score1 was 12.1 at baseline (n=71), with a decrease of -0.7 at 6 months (n=38, p=0.004), -1.4 at 12 months (n=47, p<0.0001) and -4.2 at 24 months (n=14, p=0.001). Complete radiographic erosion healing was observed in only one foot joint in which a small baseline erosion disappeared on M33 radiograph. Erosion score decrease correlated with decrease of double contours at 12 months (rho=0.45, p=0.001) and with mean SUA between M3 and M12 (rho=0, 59, p=0, 03). A total of 41 joints (hand and foot DIPs, foot II-V PIPs) could not be scored due to score specifications. Prominent diaphysis erosions were seen in 6 patients and were not allowed scoring despite improvement. Bone construction and reappearance of bone contours were striking features of improved radiographs that were not measured by the score. Ankylose of a toe joint was observed in 4 patients. Shrinking of 3 toes developed during dissolution of massive joint space/subchondral bone urate deposits. Conclusion: Urate-lowering improved gouty erosion score, in correlation with decrease of uricemia and urate crystal load. However, complete erosion recovery was seldom observed during a median follow-up of 12 months. Increased bone production and massive urate dissolution under ULD occasionally led to 2 undescribed features of gouty arthropathy: joint ankylose and shrinking of involved toes respectively References: [1]Dalbethet al, Arthritis Care Res 2007;57:1067-73. Acknowledgement: ART Viggo, Société Française de Rhumatologie Disclosure of Interests: Thomas Bardin Consultant for: Astrazeneca, Grunenthal, Horizon, Novartis, Speakers bureau: Astella, AstraZeneca, Grunenthal., Quang Dinh Nguyen: None declared, Khoi Minh Tran: None declared, Nghia Hieu Le: None declared, Duc Minh Do: None declared, Valérie Bousson: None declared, Pascal Richette Consultant for: Grunenthal, Horizon, Speakers bureau: AstraZeneca, Grunenthal, Matthieu resche-rigon: None declared